# What is the solution of 3x^3 - 1 = 0

### 2 Answers | Add Yours

The equation 3x^3 - 1 = 0 has to be solved for x.

3x^3 - 1 = 0

=> 3x^3 = 1

=> `x^3 = 1/3`

=> `x = root(3) (1/3)`

In addition, the equation has two complex roots.

`((root(3)3)*x)^3 - 1 = 0`

=> `((root(3)3)*x - 1)((root(3)3)^2*x^2 + root(3)3x + 1) = 0`

`(root(3)3)*x - 1 = 0`

=> `x = 1/root(3) 3`

`((root(3)3)^2*x^2 + root(3)3x + 1) = 0`

=> x = `(-3^(1/3) +- sqrt(3^(2/3) - 4*3^(2/3)))/(2*3^(2/3))`

=> x = `(-1 +- sqrt(1 - 4))/(2*3^(1/3))`

=> x = `(-1 +- sqrt3*i)/(2*3^(1/3))`

**The roots of the equation `3x^3 - 1 = 0` are `x = 3^(1/3)` , `x = (-1 - sqrt3*i)/(2*3^(1/3))` and **`x =(-1 + sqrt3*i)/(2*3^(1/3))`

Solution to `3x^3 - 1 = 0`

Add 1 to both sides.

`3x^3 = 1`

Divide both sides by 3

`x^3 = 1/3`

Take cubic root of each side.

`x =root(3)(1/3)`

Simplify:

`x = (root(3)(3))/3`